The Relation between Auditors' Fees for Nonaudit Services and Earnings Management - Frankel, Richard M.; Johnson, Marilyn F.; Nelson, Karen K. (The Accounting Review, 2002)
This paper examines whether auditor fees are associated with earnings management and the market reaction to the disclosure of auditor fees. Using data collected from proxy statements, we present evidence that nonaudit fees are positively associated with small earnings surprises and the magnitude of discretionary accruals, while audit fees are negatively associated with these earnings management indicators. We also find evidence of a negative association between nonaudit fees and share values on the date the fees were disclosed, although the effect is small in economic terms.